Biomass production and chemical characteristics of four grass species for bioenergy - Megalogiannis A.; Tripis G.; Papaioannou A.; Parissi Z.M.; Kyriazopoulos A.P.; Abraham E.M. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
The aim of the present study was to investigate the potential use of the grasses Avena sterilis, Bromus inermis, Hordeum bulbosum and Phalaris aquatica as bioenergy crops. Their dry matter production was measured at two phenological stages (inflorescence and fruiting) and the contents of neutral detergent fiber (NDF), acid detergent fiber (ADF), acid detergent lignin (ADL), macronutrients K, Na, Mg and ash were determined. According to the results, the dry matter production was not affected by the phenological stage, while Phalaris aquatica was the most productive followed by Avena sterilis and Bromus inermis. The higher content in NDF, ADF and ash was detected at the fruiting stage and in K, Na in the inflorescence one, while the content in ADL and Mg was not affected by the phenological stage. Bromus inermis had the lower content in NDF, ADF, ADL, Na, Mg and higher in K than the other species, while Phalaris aquatica had the lower content in ash. Combined with dry matter production, Phalaris aquatica at the fruiting stage had the optimal chemical composition for use as bioenergy crops.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)